2009
DOI: 10.4049/jimmunol.0804350
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop of IL-21 Signaling Provoked by Homeostatic CD4+CD25− T Cell Expansion Is Essential for the Development of Arthritis in Autoimmune K/BxN Mice

Abstract: Rheumatoid arthritis is a joint-specific autoimmune inflammatory disease of unknown etiology. The K/BxN mouse is a model of rheumatoid arthritis that is thought to be mainly due to autoantibody-mediated inflammatory responses. We showed previously that homeostatic proliferation of autoreactive CD4+ T cells is required for disease initiation in the K/BxN mice. In this study, we show that the homeostatically proliferating CD4+CD25− T cells produce IL-21. We generated IL-21R-deficient (IL-21R−/−) K/BxN mice and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
(45 reference statements)
2
69
0
Order By: Relevance
“…Alternatively, a recent study revealed that increased CD40L mRNA expression is associated with DNA demethylation in female patients with RA (31). Importantly, a significant correlation was noted between CD4 (34). Therefore, our studies suggest that following CD40 ligation, these therapies could paradoxically enhance the ability of B cells to survive by limiting the effects of Ab-Ag-mediated signaling through CD32B.…”
Section: Discussionmentioning
confidence: 89%
“…Alternatively, a recent study revealed that increased CD40L mRNA expression is associated with DNA demethylation in female patients with RA (31). Importantly, a significant correlation was noted between CD4 (34). Therefore, our studies suggest that following CD40 ligation, these therapies could paradoxically enhance the ability of B cells to survive by limiting the effects of Ab-Ag-mediated signaling through CD32B.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the role of IL-21 in inflammatory forms of arthritis such as RA, studies in both mice and humans suggest that IL-21 might be involved in disease progression (29)(30)(31). Young et al demonstrated that blockade of IL-21 with the IL-21R-Fc fusion protein ameliorated clinical disease activity in animal models of inflammatory arthritis, suggesting that IL-21 contributes to the pathologic process of RA (30).…”
Section: Discussionmentioning
confidence: 99%
“…Young et al demonstrated that blockade of IL-21 with the IL-21R-Fc fusion protein ameliorated clinical disease activity in animal models of inflammatory arthritis, suggesting that IL-21 contributes to the pathologic process of RA (30). Jang et al reported that IL-21 signaling is essential for the development of inflammatory arthritis in the autoimmune K/BxN mouse, a model of RA that is thought to arise mainly from autoantibody-mediated inflammatory responses (31). Those investigators demonstrated that IL-21R-deficient K/BxN mice were "completely refractory to the development of spontaneous arthritis."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, IL-21 blocking agents such as IL-21R-Fc fusion proteins have been shown a partial success in a model of SLE, the MRL-lpr mice [66], with a significant benefit in the mouse models of RA: the collagen-induced arthritis and the adjuvant induced arthritis [67,68]. This complex nature of IL-21…”
Section: Page 11 Of 35mentioning
confidence: 99%